Seasonal and circadian changes in activity rates of adult farm blue foxes - Hannu Korhonen; Paavo Niemelä (Agricultural and Food Science, 1998)
The present paper reports systematic activity rates obtained from year-round video recordings of farmbred blue foxes (Alopex lagopus) housed singly in conventional wire-mesh cages (107 cm wide x 110 long x 70 cm high). Subjects were 9 males and 13 females. Mean whole-year activity rates were slightly higher in males (394 ± 116 min/24 h; mean ± SD) than females (349 ± 111 min/24 h). Significant (P